Naming in Banten Community: An Anthroponymy Study - Muhyidin, Asep (Journal Corner of Education, Linguistics, and Literature, 2024)
The name is a symbol of a culture. It represents a specific identity or affiliation that is deeply rooted in the cultural context. Names can be derived from various sources such as geographical features, mythological characters, or personal traits, which are often reflective of the cultural values and traditions of a society. The name of Banten community is a symbol of the Banten culture. Banten community generally uses two regional languages: Banten Javanese and Banten Sundanese. This study describes the influence of foreign languages on the names of Banten community. This study used a qualitative approach. The data was taken from the names of prospective students of SMAN 1 Pontang and SMAN 4 Pandeglang. The results showed that foreign languages influenced the name of the Banten community. The foreign languages are Arabic and English. The naming consists mostly of two words. The meaning of the name is based on Islam, famous figures, time of birth, hope, and month name.